Boccaccio, friend or foe? An examination of the role of women in the Decameron - Di Sisto, Laura (Spunti e Ricerche, 2016)
Boccaccio, it seems, merely reiterates standard patriarchal views of women in moralizing tones that come to the surface from beneath the narrative, and his stated purpose as developed in the Proemio ultimately becomes problematic, contradictory and ambiguous. Though he creates multifarious images of women these images do not in reality show women freed from their confined lives but rather tend, if anything, to reinforce their traditional roles.